Cross Border Tourism and Regional Development: Case Indonesia-Timor Leste Cross Border - Werenfridus Taena; Felisisima Afoan (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2020)
This study aims to: (i) describe the perception of stakeholder about cross border tourism in Wini Indonesia and the Oecusse-timor Leste, (ii) analyze the impact of cross border tourism on the regional development. The study was conducted in Wini North Insana Subdistrict, North Central Timor Regency in April-June 2019. The study used a survey method using descriptive analysis to achieve the first aim and mathematical analysis to achieve the second aim. The results showed that tourist decides to go to Wini as cross border tourism cause the complete attraction covers beach, mountain, cross border tourism, fish culinary or the large number of attractions (90%); then unique tourist attraction (80%).  The result also showed the economic agglomeration 2,03; that moderate agglomeration and its increasingly strengthening the region as a new growth center, also shown by an increase of growth economic 68,79% as regional development indicator.